Pengembangan Sistem Informasi Manajemen Akademik Sekolah Dasar Untuk Pendaftaran Dan Pendataan Ulang Siswa (Studi Kasus Pada Sekolah Dasar Negeri Dinoyo 1 Malang) - Nyoman Puja Satria Wibawa; Ismiarta Aknuranda; Satrio Agung Wicaksono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Dinoyo 1 Elementary School is one of the primary education institutions in Malang city. The school has passed 8 National Standards of Education and has accreditation A. In the process of registering new students it is still done manually, causing problems in managing registration data. Student data is the official identity of each student, every semester in Dinoyo 1 Elementary School conducts the process of recollecting of the student's data that also done manually which causes the school experiencing difficulties in managing the student's data. It is necessary to have an information system that can handle these problems. In developing the information system, it is done using Waterfall model and implemented as a website. At the requirements analysis stage, 44 functional requirements and 1 nonfunctional requirement are obtained. The implementation is done using CodeIgniter framework with the Model-View-Controller pattern. Afterward, several functions are tested using validation testing. The results are all valid. Testing is also done using compatibility testing. The result shows that the system runs with Critical Issues on Firefox browser version 63 and Chrome version 70, then there are major issues if the site is accessed via Internet Explorer version 11 and Android version 4 browsers or earlier.